1990
DOI: 10.3168/jds.s0022-0302(90)78749-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I in Dairy Cows: Relationships Among Energy Balance, Body Condition, Ovarian Activity, and Estrous Behavior

Abstract: The objective was to determine relationships among concentrations of insulin-like growth factor-I in serum, energy balance, body condition, and ovarian activity during early lactation. From 0 to 12 wk postpartum, 11 pluriparous Holstein cows were individually fed a total mixed diet and bled twice weekly for quantification of insulin-like growth factor-I and progesterone. Estrous behavior was monitored twice daily and body condition scores were recorded weekly. Individual feed intake and milk production were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
128
4
15

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(168 citation statements)
references
References 25 publications
21
128
4
15
Order By: Relevance
“…Preliminary studies in our laboratory have also found a positive correlation between IGF-I and estrogen in serum of early postpartum dairy cows. Improvement in energy balance not only leads to an increase in secretion of IGF-I as previously discussed, but also progesterone during the first and second estrous cycles postpartum [81,83,86]. Beam and Butler [8,9] also found that plasma IGF-I levels were 40-50% higher during the first 2 weeks postpartum in dairy cows when the first dominant follicle (DF) ovulated compared with those with non-ovulatory follicles.…”
Section: Igf-i and Hypothalamo-pituitary Functionmentioning
confidence: 89%
See 2 more Smart Citations
“…Preliminary studies in our laboratory have also found a positive correlation between IGF-I and estrogen in serum of early postpartum dairy cows. Improvement in energy balance not only leads to an increase in secretion of IGF-I as previously discussed, but also progesterone during the first and second estrous cycles postpartum [81,83,86]. Beam and Butler [8,9] also found that plasma IGF-I levels were 40-50% higher during the first 2 weeks postpartum in dairy cows when the first dominant follicle (DF) ovulated compared with those with non-ovulatory follicles.…”
Section: Igf-i and Hypothalamo-pituitary Functionmentioning
confidence: 89%
“…However, in a later study McGuire et al [57] reported for the first time that in two days of feed deprivation, circulating concentrations of IGF-I reduced by 50% in lactating cows. Spicer et al [83] reported that short-term fasting in heifers decreased plasma IGF-I, and Lucy et al [55] found that cows fed low energy diets had lower plasma IGF-I. In suckled and/or non-pregnant beef cows, feed restriction resulted in a marked depression in serum concentrations of IGF-I, whereas insulin and glucose were only depressed slightly [72,74].…”
Section: Effect Of Nutritional Status On Circulat-ing Concentrations mentioning
confidence: 99%
See 1 more Smart Citation
“…Milk yield and associated energy requirements are often mentioned as cause for vague oestrus expression. However, the results of the studies that have been reported so far are inconclusive (10,16,23,25,26). Environmental factors are the third group of factors affecting oestrus detection.…”
Section: Introductionmentioning
confidence: 93%
“…10, might be the reason for the differences. Spicer et al (23) and Villa-Godoy et al (26) reported that the expression of oestrus was not affected in second and third…”
mentioning
confidence: 99%